2021
DOI: 10.1007/s00296-021-04829-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of mental health disorders in patients with RA during the COVID-19 pandemic: a possible surge and solutions

Abstract: Depression is a common co-morbidity among rheumatoid arthritis (RA) patients, which may translate into difficulty performing activities of daily living. COVID-19 is an unprecedented disaster that has disrupted lives worldwide and led to a rise in the incidence of mental health disorders. Given the widespread economic devastation due to COVID-19, many RA patients, already susceptible to mental illness, maybe at an increased risk of inaccessibility to medical care, accentuated stress, and consequent worsening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 56 publications
0
33
0
2
Order By: Relevance
“…Due to the economic and social devastation due to COVID-19, many patients may be at an increased risk of having difficulty to access to medical care, accentuated stress, and worsening of mental health disorders, such as anxiety or depression. A recent review by Bathia et al found that there was a significant association between COVID-19 pandemic and the adverse impact on the mental health and daily living activities in rheumatology patients [32]. In our survey, 14.1% (41) of the patients who were receiving psychiatric medication to treat their comorbidities had to discontinue it.…”
Section: Discussionmentioning
confidence: 61%
“…Due to the economic and social devastation due to COVID-19, many patients may be at an increased risk of having difficulty to access to medical care, accentuated stress, and worsening of mental health disorders, such as anxiety or depression. A recent review by Bathia et al found that there was a significant association between COVID-19 pandemic and the adverse impact on the mental health and daily living activities in rheumatology patients [32]. In our survey, 14.1% (41) of the patients who were receiving psychiatric medication to treat their comorbidities had to discontinue it.…”
Section: Discussionmentioning
confidence: 61%
“…Hypertension was the most common comorbidity (142; 29%) and the median (IQR) CCI was 1.0 (1.0‐2.0). The median (IQR) number of health care visits within the MGB system in the last 6 months of 2019 (July 1, 2019, to December 31, 2019), preceding the pandemic, was 16 ( 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ). At the time of the survey, the mean (SD) disease activity was 74.6 (19.9).…”
Section: Resultsmentioning
confidence: 99%
“…Although shielding practices are critical to reducing risks of COVID‐19 and controlling the ongoing pandemic, they do come at substantial personal and societal costs. Indeed, previous studies of the general population and participants with rheumatic diseases have established the negative impacts of the pandemic on mental health, including anxiety and depression, likely driven in part by the need for shielding practices, which contribute to social isolation ( 24 , 25 , 26 , 27 , 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…That study also established a straight correlation between parents' and children's anxiety and depression scores. Bhatia et al [91] draw attention to the vicious circle uniting physical and mental wellbeing. Based on the systemic review data, patients with RA may suffer from aggravation of pain and disease activity in case of depression [92].…”
Section: Covid-19 From the Ards Patient's Standpointmentioning
confidence: 99%